Becoming good ancestors : how we balance nature, community, and technology - Ehrenfeld, David (Oxford University Press, 2009)
A brilliant writer and gifted "big picture" thinker, David Ehrenfeld is one of America's leading conservation biologists. Becoming Good Ancestors unites in a single, up-to-date framework pieces written over two decades, spanning politics, ecology, and culture, and illuminating the forces in modern society that thwart our efforts to solve today's hard questions about society and the environment. The book focuses on our present-day retreat from reality, our alienation from nature, our unthinking acceptance of new technology and rejection of the old, the loss of our ability to discrimin